Effects of two different dexamethasone dosing regimens on ventilator-free days and long-term mortality in COVID-19 patients with moderate-to-severe ARDS: the REMED randomized clinical trial - Maláska, Jan; Stašek, Jan; Máca, Jan; Kutěj, Martin; Duška, František; Kafka, Petr; Klementová, Olga; Doubravská, Lenka; Hruda, Jan; Fencl, Marek; Gabrhelík, Tomáš; Číž, Libor; et al. (European journal of medical research, 2024)
BACKGROUND: Dexamethasone 6 mg in patients with severe COVID-19 has been shown to decrease mortality and morbidity. The effects of higher doses of corticosteroid, that would further increase anti-inflammatory effects, are uncertain. The objective of our study was to assess the effect of 20 mg dexamethasone vs. 6 mg dexamethasone intravenously in patients with moderate-to-severe acute respiratory distress syndrome (ARDS) and COVID-19. METHODS: In a multicenter, open-label, randomized trial conducted in nine hospitals in the Czech Republic, we randomized adult patients with ARDS and COVID-19 requiring high-flow oxygen, noninvasive or invasive mechanical ventilation to receive either intravenous high-dose dexamethasone (20 mg/day on days 1-5, 10 mg/day on days 6-10) or standard-dose dexamethasone (6 mg/d, days 1-10). The primary outcome was 28-day ventilator-free days. The five secondary outcomes were 60-day mortality, C-reactive protein dynamics, 14-day WHO (World Health Organization) Clinical Progression Scale score, adverse events and 90-day Barthel index. The long-term outcomes were 180- and 360-day mortality and the Barthel index. The planned sample size was 300, with interim analysis after enrollment of 150 patients. RESULTS: The trial was stopped due to a lack of recruitment, and the follow-up was completed in February 2023. Among 234 randomized patients of 300 planned patients, the primary outcome was available for 224 patients (110 high-dose and 114 standard-dose dexamethasone; median [interquartile range (IQR)] age, 59.0 [48.5-66.0] years; 130 [58.0%] were receiving noninvasive or invasive mechanical ventilation at baseline). The mean number of 28-day ventilator-free days was 8.9 (± 11.5) days for high-dose dexamethasone and 8.0 (± 10.7) days for standard-dose dexamethasone, with an absolute difference of + 0.81 days (95% CI - 2.12-3.73 days). None of the prespecified secondary outcomes, including adverse events, differed between the groups. CONCLUSIONS: Despite not reaching its prespecified enrollment, there was no signal to either benefit or harm high-dose dexamethasone over standard-dose dexamethasone in patients with COVID-19 and moderate-to-severe ARDS. Trial registration Trial registration: ClinicalTrials.gov Identifier: NCT04663555. Registered 10 December 2020, https://clinicaltrials.gov/study/NCT04663555?term=NCT04663555&rank=1 and EudraCT: 2020-005887-70.
Keywords: umělé dýchání; dexamethason; Randomized clinical trial; Humans; lidé středního věku; syndrom dechové tísně; Dose-Response Relationship, Drug; Female; Aged; výsledek terapie; senioři; lidé; Respiratory Distress Syndrome; COVID-19; ARDS; ženské pohlaví; Male; Middle Aged; Ventilator-free days; Dexamethasone; Treatment Outcome; Long-term outcomes; Czech Republic; farmakoterapie COVID-19; vztah mezi dávkou a účinkem léčiva; Česká republika; mužské pohlaví; SARS-CoV-2; Respiration, Artificial; COVID-19 Drug Treatment